Analisi Regulatory Impact Assesment (RIA) untuk Mengevaluasi Kebijakan Penanganan Pandemi Covid-19 di Kota Tanggerang Selatan - Shinta Wahyuni Chairuddin; Evi Satispi (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2023)
Efforts that must be made by the regional government in tackling or breaking the chain of the Covid-19 pandemic are issuing regulations governing community activities and actions that need to be taken by the regional government. This effort has been made by the City Government of South Tangerang by issuing Mayor Regulation no. 13 of 2020 concerning Implementation of Large-Scale Social Restrictions in the Context of Handling Corona Virus Disease 2019. The purpose of this research is to evaluate the Regulation of Mayor using a qualitative descriptive method with a normative legal study approach using Regulatory Impact Analysis (RIA). The results of the study concluded that it was necessary to revise the Regulation of Mayor, especially on the points: social organization activities, the obligation of workplace leaders to ensure that employees do not have co-morbidities, the obligation to provide temperature test kits, regulation of worship activities, explanations about public facilities, the obligation to use masks, community rights, provision of incentives and vaccines, and criteria for administrative sanctions.